2020
DOI: 10.3390/ijerph17082639
|View full text |Cite
|
Sign up to set email alerts
|

Training and Competition Load in Female Basketball: A Systematic Review

Abstract: The scientific literature on women’s basketball is still limited, mainly in performance parameters. The purpose of this study was to analyse the state of art on the internal and external loads supported by female basketball players during sports practice. The design of this research is theoretical. The most relevant databases were searched for pertinent published studies according to the following keywords: “basketball”, “female” or “woman”, “training” or “competition”, “load” or “demand”. Of the 644 studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 20 publications
4
54
0
7
Order By: Relevance
“…Through the kappa index, as used in other reviews [ 5 , 7 , 8 , 10 ], a value of 0.755 was obtained for interobserver reliability, indicating a substantial agreement between observers [ 12 ]. The quality of the articles included in this review is confirmed by the following indicators: the average quality score of the articles was 85.7%; 75 articles had a score above 75%, and below 100% (excellent methodological quality); 7 articles exposed scores between 51% and 75% (good methodological quality); and no article had a score equal to or less than 50% (low methodological quality).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Through the kappa index, as used in other reviews [ 5 , 7 , 8 , 10 ], a value of 0.755 was obtained for interobserver reliability, indicating a substantial agreement between observers [ 12 ]. The quality of the articles included in this review is confirmed by the following indicators: the average quality score of the articles was 85.7%; 75 articles had a score above 75%, and below 100% (excellent methodological quality); 7 articles exposed scores between 51% and 75% (good methodological quality); and no article had a score equal to or less than 50% (low methodological quality).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the quality of the studies, the risk-bias quality form used by Gómez-Carmona [ 5 ], Reina [ 7 ], Sarmento [ 8 ] and García-Santos [ 10 ], adapted from the original version developed by Law [ 11 ], was adopted. This evaluation is composed of 16 items and was performed by two researchers, with valuable expertise on this topic.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations